2016
DOI: 10.1308/rcsann.2016.0106
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic proton pump inhibitors in femoral neck fracture patients – A life - and cost-saving intervention

Abstract: INTRODUCTION Acute gastrointestinal stress ulceration is a common and serious complication of trauma. Prophylactic proton pump inhibitors (PPIs) or histamine receptor antagonists have been used in poly-trauma, burns and head and spinal injuries, as well as on intensive care units, for the prevention of acute gastric stress ulcers. METHODS We prospectively studied the use of prophylactic PPIs in with femoral neck fracture patients, gathering data on all acute gastric ulcer complications, including coffee-groun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
27
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 33 publications
(31 reference statements)
1
27
1
Order By: Relevance
“…Only 0.65% of patients in our study developed perioperative acute UGIB, which is lower than the reported rate in similar populations …”
Section: Discussioncontrasting
confidence: 87%
See 4 more Smart Citations
“…Only 0.65% of patients in our study developed perioperative acute UGIB, which is lower than the reported rate in similar populations …”
Section: Discussioncontrasting
confidence: 87%
“…Only 0.65% of patients in our study developed perioperative acute UGIB, which is lower than the reported rate in similar populations. [4][5][6] Of the previously reported risk factors for UGIB, a history of PUD was found to be a strong risk factor in our study. We did not find associations between UGIB and active smoking, or blood group O.…”
Section: Discussionsupporting
confidence: 47%
See 3 more Smart Citations